2010
DOI: 10.1007/s11882-010-0096-0
|View full text |Cite
|
Sign up to set email alerts
|

Rhinosinusitis and Asthma: A Link for Asthma Severity

Abstract: The term rhinosinusitis describes an inflammation of the mucosal lining of the nose and sinuses; however, recent evidence points to the need to differentiate patients with chronic rhinosinusitis without nasal polyps from those with nasal polyps. Asthma comorbidity is especially common in nasal polyp disease and may be associated with aspirin-exacerbated respiratory disease. Of interest, asthma comorbidity is uncommon in some parts of the world but common in others. A further analysis of the inflammatory patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
2
4

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 37 publications
(34 reference statements)
3
57
2
4
Order By: Relevance
“…Recent studies suggest that the Staphylococcus aureus enterotoxins (SAEs) may act as superantigens by amplifying eosinophilic inflammation and possibly inducing local IgE formation in severe persistent airway disease in AERD (Kowalski et al, 2011). Bachert et al also reported that within the group for chronic rhinosinusitis with nasal polyp, patients with Th 2 -biased eosinophilic inflammation have increased risk of severe asthma development (Bachert et al, 2010). However, nasal tissue and bronchial biopsies reveal extensive eosinophilic infiltration and degranulated mast cells in patients with AERD.…”
Section: Proposed Mechanisms For the Interaction Between Upper And Lomentioning
confidence: 99%
“…Recent studies suggest that the Staphylococcus aureus enterotoxins (SAEs) may act as superantigens by amplifying eosinophilic inflammation and possibly inducing local IgE formation in severe persistent airway disease in AERD (Kowalski et al, 2011). Bachert et al also reported that within the group for chronic rhinosinusitis with nasal polyp, patients with Th 2 -biased eosinophilic inflammation have increased risk of severe asthma development (Bachert et al, 2010). However, nasal tissue and bronchial biopsies reveal extensive eosinophilic infiltration and degranulated mast cells in patients with AERD.…”
Section: Proposed Mechanisms For the Interaction Between Upper And Lomentioning
confidence: 99%
“…Distintos estudos publicaram a associação de RSC com pólipos à asma (39,40) e mostraram que 30% dos pacientes com RSC com pólipos tem asma associada, enquanto 7% dos asmáticos apresenta RSC com pólipos (12,41) .…”
Section: Rsc E Asmaunclassified
“…Bachert et al (39) (2010) publicaram um estudo de coorte com amostras de 600 pacientes em nove centros europeus em que analisaram a distribuição da doença na via aérea inferior, em diferentes grupos de pacientes com RSC. A asma brônquica estava presente em 45% dos pacientes com RSC com polipose nasossinusal.…”
Section: Rsc E Asmaunclassified
See 2 more Smart Citations